The social mood reader: Mapping citizen engagement using the semantic web and supercomputing - Balnaves, Mark (ANZCA, 2011)
Actual experiments in e-government and participatory online decision-makinghave, however, often proved disappointing. Traditional forms of governmentpolicy making and political organization, based upon centralised andhierarchical structures, one-to-many communications, and ‘push’ models ofstate–citizen interaction, have struggled to adapt to the decentralised, manyto-many forms of interaction of the Internet (Flew & Young 2005).Flew and Young’s quote above gets straight to the point. Participatory online decisionmakinginvolves more than consultation or sophisticated ways of delivering information tocitizens, although these of course are important. Online decision-making presupposes asocial-organisational structure that makes real decision-making possible. In this paper theauthor provides an overview of the use of sophisticated semantic web tools to calculatecitizen mood and the kinds of organisational structure emerging in local governmentjurisdictions that allow for actual decision-making.